Antioxidant and antitumor effects of polysaccharides from the fungus Pleurotus abalonus. (25th July 2015) - Ren, Daoyuan; Jiao, Yadong; Yang, Xingbin; Yuan, Li; Guo, Jianjun; Zhao, Yan
Highlights: PAP is a heteropolysaccharide isolated from Pleurotus abalonus . PAP has strong free radicals-scavenging and antioxidant capacities in vitro. PAP had a prominent antiproliferative effect against LoVo cancer cells. PAP could increase the generation of intracellular ROS which was a critical mediator in PAP-induced cell growth inhibition. PAP is a good candidate product for dietary supplement and therapeutic application. Abstract: Dietary supplement of edible Pleurotus abalonus ( P. abalonus ) rich in fungal polysaccharides is associated with anticancer health benefit. We here isolated the polysaccharides (PAP) from the fruiting bodies of P. abalonus, and evaluated the antiproliferative activity of the polysaccharides in human colorectal carcinoma LoVo cells. HPLC analysis showed that PAP consisted of d -mannose, d -ribose, l -rhamnose, d -glucuronic acid, d -glucose and d -galactose, and their corresponding mole percentages were 3.4%, 1.1%, 1.9%, 1.4%, 87.9% and 4.4%, respectively. PAP was shown to exert a high antioxidant activity in vitro and a dose-dependent antiproliferative effect against LoVo cancer cells. Flow cytometry analysis demonstrated that PAP exhibited a stimulatory effect on apoptosis of LoVo cells, and induced the cell-cycle arrest at the S phase. We also found that PAP could increase the generation of intracellular ROS which was a critical mediator in PAP-induced cell growth inhibition. These findings suggest that PAP may serve as a potential novel dietary agent for human colon cancer chemoprevention.